DETERMINASI AUDITOR SWITCHING: PERAN PROFITABILITAS, FINANCIAL DISTRESS, DAN OPINI GOING CONCERN DI SEKTOR PERTAMBANGAN INDONESIA - Kurnia, Denny; Hapsari, Denny Putri; Almadina, Salsabila Diva (Journal of Information System, Applied, Management, Accounting and Research, 2025)
This study aims to examine the influence of profitability ratio, financial distress, and going concern audit opinion on auditor switching among mining companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. Auditor switching is a critical issue in accounting and auditing, as it relates to auditor independence and financial statement transparency. This research employs a quantitative approach using secondary data derived from audited financial reports. The independent variables in this study include Return on Assets (ROA) as a measure of profitability, Debt to Equity Ratio (DER) as an indicator of financial distress, and going concern audit opinion measured using a dummy variable. Auditor switching, as the dependent variable, is also measured using a dummy variable. Data analysis was conducted using logistic regression to evaluate the impact of each variable on auditor switching decisions. The results reveal that profitability and going concern audit opinion have a positive and significant effect on auditor switching, whereas financial distress does not have a significant influence. These findings support agency theory and highlight the importance of financial performance and audit opinion in managerial decision-making. This study contributes to the literature on auditor switching, particularly within the mining sector, which remains underexplored in the Indonesian context.